Modeling the influence of digital technical competence in animation creation on employability of vocational high school animation students using PLS-SEM - Mardi, Mardi; Ekohariadi, Ekohariadi; Sutiadiningsih, Any; Wibowo, Theodorus Wiyanto; Suhartini, Ratna (Edelweiss Applied Science and Technology, 2025)
This study investigates the impact of digital technical competence in animation creation on the employability of vocational high school animation students using Partial Least Squares Structural Equation Modeling (PLS-SEM). The research highlights the importance of 21st-century skills, such as creativity, critical thinking, and collaboration, and their relevance to employability in digital industries. A survey conducted among 54 vocational students in Surabaya revealed that technical competencies, particularly in animation, significantly affect employability. The study’s model demonstrates strong validity and reliability, confirming that the development of digital technical skills in animation is crucial for improving students’ readiness for the job market. Findings emphasize the necessity of integrating these competencies into education systems to prepare students for evolving industry demands.